Piety, music and gender transformation: reconfiguring women as culture bearing markers of modernity and nationalism in Bangladesh - Huq, Samia (© 2011 Taylor & Francis., 2016)
This article was published in Inter-Asia Cultural Studies [ © 2011 Taylor & Francis ] and the definite version is available at: http://dx.doi.org/10.1080/14649373.2011.554650 The Article's website is at: http://www.tandfonline.com/doi/abs/10.1080/14649373.2011.554650